Prospects for Personality Development of Gifted Children - Gorbaneva E. V. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the article is devoted to the issue of possible prospects for personality development of gifted children. The author’s approach is based on the results of research made by American psychologist L. Terman. Analyzing the subject, the author pays special attention to acceleration in personality development of the gifted children as one the educational strategies. The author is also touching upon the issue of establishing a special school for gifted children. The general conclusion made in the article is that various manifestations of giftedness and a child’s advances in various fields at an early age regretfully cannot guarantee success in his future path of self-realization.
Keywords: одаренные дети; одаренность; giftedness; gifted children; перспективы личностного развития; стратегии обучения одаренных детей; однородные классы; prospects for personal development; educational strategies for gifted children; homogeneous classes